Making prisoners accountable: are contingency management programs the answer? - Gendreau, Paul (Criminal justice and behavior, 2014)
There has been a renewed interest among some prison policy makers to hold inmates more accountable for their actions. The belief is that inmates require more structure and discipline in their daily activities and must demonstrate that they have earned privileges that can lead to their early release. A meta-analysis and narrative review was undertaken to determine the utility of contingency management (CM) programs for improving inmates? performance (e.g., prison adjustment, educational/work skills) and to generate a list of program principles for managing CM programs effectively. The study finds that CM programs produce robust gains in a variety of behaviors (e.g., pro-social behaviors, education, work assignments, etc.) in prison settings. As a result, the authors provide a list of ?what works? principles, categorized into implementation and treatment strategies for administering effective CM programs in prison.